PEMBERDAYAAN KELOMPOK PEMUDA DALAM BUDIDAYA IKAN NILA - Luda Sofiah; Jumadi Jumadi; Aniatul Agustini; Imam Maulana Putra; Masriyadi Masriyadi; Kardi Kardi; Dede Kurnia; Basrowi Basrowi; Furtasan Ali Yusuf (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Tilapia farming ranging from seed to large commercially using floating nets is still small, while the potential for aquaculture activities in general freshwater opportunities is still large. The level of demand for tilapia consumers tends to increase every year along with the increase in population. Maintenance containers in floating net caramba can maintain fish with high density to increase fish production. Karamba floating nets also have stable water quality so that production can be higher. Technical information on tilapia rearing in floating net caramba is needed so that fish production can be increased. This community service aims to determine the effect of empowering youth groups on tilapia cultivation on improving the community's economy. This method of community service through counseling and coaching. Data collection through pre-test and post-test. The results of this community service show that there is a significant influence on increasing community knowledge about tilapia farming